A conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate and preparation method thereof
By adopting low-chromium and high-chromium composition gradient transition design on stainless steel substrates, combining sintering and laser melting technology, the contradiction between conductivity, corrosion resistance and forming performance of metal bipolar plate materials is solved, and efficient fuel cell plate production is achieved , improves performance and production efficiency.
Patent Information
- Application Number
- CN202211701728.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-28
Smart Images

Figure CN116039179B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composition gradient thin plates and fuel cells, and relates to a conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate and a preparation method thereof. Background Art
[0002] Bipolar plates are a typical component of fuel cells. Currently, metal bipolar plates are widely used in fuel cells due to their high gas barrier properties, small size, and suitability for mass production.
[0003] The forming properties of the metal bipolar plate substrate directly affect the manufacturing difficulty of the bipolar plate. At the same time, both the conductivity and corrosion resistance will affect the performance of the fuel cell. However, in the existing metal bipolar plate products, it is difficult for commonly used metal materials to achieve compatibility of conductivity, corrosion resistance and forming properties. This factor restricts the improvement of the comprehensive performance of the product. For example, an oxide layer is easily formed on the surface of titanium alloy sheets, which has good corrosion resistance, but poor conductivity and forming properties; niobium metal sheets have excellent corrosion resistance and forming properties, but poor conductivity and high cost. Stainless steel sheets have good forming properties, but poor conductivity and corrosion resistance. During service, a large amount of ions are precipitated, which poisons components such as proton exchange membranes.
[0004] On the other hand, composition gradient materials, as a new material structure, have received increasing attention in recent years.
[0005] A search of existing literature found that the Chinese patent publication number is: CN105643215A, and the name is: Direct forming manufacturing method and process device of metal-based multilayer / gradient composite sheet. The technology includes: preparing composite sheet on the basis of rolled sheet through processes such as cleaning, powder spreading, heating and melting, and rolling. The disadvantage of this technology is that it limits the thickness ratio of the gradient layer to the substrate. Similar to the coating, there is a problem of premature cracking due to the uncoordinated deformation of the thin gradient layer; at the same time, its gradient layer does not take into account the high-chromium stainless steel component, and does not provide a solution to the contradiction between corrosion resistance, conductivity and formability of fuel cell bipolar plates.
[0006] After further literature search, it was found that the Chinese patent publication number is: CN109735766A, and the name is: A gradient ultrafine grain structure low carbon microalloy steel and its preparation method, which includes: combining the asynchronous rolling and shearing composite mechanism with the strain-induced ferrite phase transformation mechanism to obtain a structure morphology with a gradient distribution of grain size in the thickness direction. The disadvantage of this technology is that the improvement of the forming performance is limited only through the grain gradient design, and it is difficult to achieve the compatibility of electrical conductivity, corrosion resistance and forming performance.
[0007] After further literature search, it was found that the Chinese patent publication number is: CN106269865A, and the name is: Rolling method of multi-layer stainless steel metal composite plate. The technology includes: using layer rolling to hot-roll martensitic stainless steel and austenitic stainless steel to improve the comprehensive mechanical properties of the steel plate. The disadvantage of this technology is that there is a clear interface between different layers of plates, and the composition difference on both sides of the interface is obvious. During the stamping process, interlayer stress cracking is prone to occur, which affects the performance of the final product.
[0008] Patent CN101257118A discloses a bipolar plate for fuel cells and a method for preparing a carbon-chromium film on its surface. The bipolar plate is composed of a stainless steel sheet substrate and carbon-chromium films on both sides of the substrate. The thickness of the carbon-chromium film is in the micro-nano range and is prepared by an arc ion plating method, wherein the substrate passivation film is removed by ion sputtering before plating, and the ions used come from the glow plasma of an inert gas or from the arc plasma of a metal target evaporation. During the film deposition process, a single film with uniform composition and a gradient film with a continuously changing composition from the inside to the outside are obtained by controlling the plating parameters. However, the carbon-chromium film on the surface of the patent is extremely brittle. Even if the composition is transitioned, the surface corrosion-resistant conductive layer cannot withstand plastic deformation. Therefore, the corrosion-resistant conductive layer can only be added piece by piece after the plate is stamped. Summary of the invention
[0009] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate and a preparation method thereof. The present invention comprehensively utilizes the formability of 316L stainless steel and the passivation ability of high-chromium stainless steel to solve the contradiction between the corrosion resistance, conductivity and formability of fuel cell metal plate materials, and can meet the needs of large-scale rapid production.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] One of the technical solutions of the present invention is to provide a conductive, corrosion-resistant, high-ductility gradient stainless steel substrate, the two side surfaces of the gradient stainless steel substrate are low-chromium stainless steel and high-chromium stainless steel respectively, the middle layer is a transition layer with a gradient transition of components along the thickness direction, wherein the thickness of the low-chromium stainless steel accounts for 50-70% of the total thickness, the chromium content of the high-chromium stainless steel is 25-30 wt.%, the thickness of the high-chromium stainless steel accounts for 5-15% of the total thickness, and the rest is the transition layer. The low-chromium stainless steel ensures the formability of the plate, the high-chromium stainless steel ensures the corrosion resistance and conductivity of the plate, and the transition layer ensures the coordinated deformation ability of the whole plate.
[0012] One of the technical solutions of the present invention is to provide a method for preparing a conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate, the preparation method comprising the following steps:
[0013] (1) Stainless steel powders with different chromium contents are layered to obtain initial plates;
[0014] (2) Annealing the initial plate to remove internal stress;
[0015] (3) The initial plate is thinned by differential roller rolling to obtain a gradient thin plate;
[0016] (4) The gradient thin plate is annealed to remove internal stress and obtain a gradient stainless steel substrate.
[0017] Furthermore, the stainless steel powders with different chromium contents in step (1) are divided into low-chromium stainless steel powder, high-chromium stainless steel powder and transition layer powder, which are obtained by mixing commercial 316L stainless steel powder and pure chromium powder, or directly using homogeneous pre-alloyed powder;
[0018] The low chromium stainless steel powder is commercial 316L stainless steel powder or homogeneous pre-alloyed powder with similar composition. The proportion of each element in the low chromium stainless steel powder is Cr: 16-18 wt.%, Ni: 10-14 wt.%, Mo: 2-3 wt.%, Mn≤2 wt.%, C≤0.03 wt.%, Si≤1 wt.%, and the rest is Fe;
[0019] The high chromium stainless steel powder is directly obtained by using homogeneous pre-alloyed powder, or by mixing commercial 316L stainless steel powder with pure chromium powder (purity of pure chromium powder is above 99.9%). The proportion of each element in the high chromium stainless steel powder is Cr: 25-30 wt.%, Ni≤12.5 wt.%, Mo: 1.5-3 wt.%, Mn≤2 wt.%, C≤0.03 wt.%, Si≤1 wt.%, and the rest is Fe;
[0020] The proportion of each element in the transition layer powder transitions layer by layer from a high-chromium stainless steel powder component to a low-chromium stainless steel powder component along the thickness direction, and the number of the transition layers is 2-8 layers.
[0021] As a preferred technical solution, in step (1), the low chromium stainless steel powder and the high chromium stainless steel powder are both spherical powders, and the particle size of the powders is 15-53 μm.
[0022] Furthermore, the layered molding technique in step (1) includes powder sintering or laser melting (SLM).
[0023] As a preferred technical solution, if laser melting is used to prepare the initial plate in step (1), the process parameter settings corresponding to the transition layer composition should be determined based on the relationship between the current layer and the chromium content in the low-chromium stainless steel powder and the high-chromium stainless steel powder, and linear interpolation should be performed using the parameters selected for the low-chromium stainless steel powder and the high-chromium stainless steel powder.
[0024] Furthermore, in step (1), the external pressure for sintering the powder is 25-35 kPa, the holding time is 80-120 min, and the sintering temperature is 900-1100 °C.
[0025] Furthermore, in step (1), the laser spot diameter of the laser melting is 50-70 μm, the scanning interval is 65-105 μm, and the single layer melting thickness is 20-40 μm;
[0026] The laser power for low-chromium stainless steel powder is 160-180 W, and the laser scanning speed is 700-900 mm / s;
[0027] The laser power for high chromium stainless steel powder is 300-400 W, and the laser scanning speed is 800-1100 mm / s.
[0028] Furthermore, after step (2), the initial plate obtained by laser melting is separated from the substrate by wire cutting, wherein the wire cutting is a fast-wire electric spark wire cutting process, and the molybdenum wire speed of the wire cutting is 8-10 m / s.
[0029] Furthermore, the annealing treatment in steps (2) and (4) is carried out under an inert gas protection environment, at a temperature of 700-900°C, for 15-30 min, and then naturally cooled.
[0030] Furthermore, in the differential roller rolling process in step (3), the differential rollers are an upper high-speed roller and a lower low-speed roller of the same diameter, the diameter of the differential rollers is 80-100 mm, the high-speed roller is in contact with the high-chromium content stainless steel, the low-speed roller is in contact with the low-chromium content stainless steel, the rotation speed of the low-speed roller is 5-20 r / min, and the rotation speed of the high-speed roller is 1.2-1.5 times that of the low-speed roller, so as to alleviate the difference in elongation caused by the difference in deformation capacity at different thickness positions of the plate.
[0031] Furthermore, the gradient stainless steel substrate is directly used for stamping, or is electrochemically treated after stamping to ensure that a continuous, dense and extremely thin passivation film is formed on the surface to improve the corrosion resistance and electrical conductivity;
[0032] The electrochemical treatment includes a first stage and a second stage, wherein the applied voltage in the first stage is 0.5-0.8 V / SHE and the treatment time is 800-1000 s, and the applied voltage in the second stage is 1.0-1.4 V / SHE and the treatment time is 3200-3600 s, and the solutions used in both stages are 0.1-1 mol / L dilute sulfuric acid solutions.
[0033] Existing research shows that high-chromium stainless steel will form a thin and dense passivation film after electrochemical passivation treatment, which can ensure both corrosion resistance and electrical conductivity. Based on the good formability of 316L stainless steel, the high chromium content is used as the outer surface and the composition gradient transition design of 316L stainless steel along the thickness direction of the plate can achieve the compatibility of corrosion resistance, electrical conductivity and formability of the plate, which is suitable for large-scale batch manufacturing of the plate.
[0034] After the steps of powder sintering / laser melting, annealing, wire cutting separation, differential roller rolling, heat treatment, etc., a composition gradient thin plate is formed, which presents a transition design from high chromium content to low chromium content stainless steel in the thickness direction. Through the coordinated deformation between different components, good ductility is achieved, which can be used for fuel cell plate stamping. After the formed plate is electrochemically treated, a thin and dense passivation layer is formed on the high chromium side surface, corresponding to the air intake side of the fuel cell plate, and has good corrosion resistance and electrical conductivity.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] (1) The present invention forms a gradient thin plate by designing a gradient transition of the composition in the thickness direction of the plate, and the metal plate surface has excellent corrosion resistance, electrical conductivity and forming performance;
[0037] (2) The present invention directly prepares the initial plate from powders of different compositions by sintering or additive manufacturing, and the plate can be used for stamping after a relatively small number of fine rolling passes. The formed plate can be obtained by a short electrochemical treatment to obtain the final product. The process route is short and the production efficiency is high. The plate is a composition gradient plate suitable for large-scale and rapid production of fuel cell bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Schematic diagram of the preparation method of the conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate in Examples 1 and 2 of the present invention;
[0039] Figure 2 This is a schematic diagram of a method for preparing a conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate in Example 3 of the present invention;
[0040] Figure 3 Schematic diagram of powder sintering in an embodiment of the present invention;
[0041] Figure 4 Schematic diagram of laser melting in an embodiment of the present invention;
[0042] Figure 5 A schematic diagram of an annealing process in an embodiment of the present invention;
[0043] Figure 6 Schematic diagram of wire cutting separation in an embodiment of the present invention;
[0044] Figure 7 Schematic diagram of differential roller rolling in an embodiment of the present invention;
[0045] Figure 8 Schematic diagram of electrochemical treatment in an embodiment of the present invention.
[0046] Description of the markings in the figure:
[0047] 1—gradient stainless steel substrate, 1-1—high chromium content stainless steel, 1-2—low chromium content stainless steel, 2—push rod, 3—mold, 4—powder, 5—base plate, 6—scraper, 7—laser, 8—galvanometer, 9—powder cylinder, 10—forming cylinder, 11—recovery cylinder, 12—molybdenum wire, 13—high speed roller, 14—low speed roller, 15—auxiliary electrode, 16—sulfuric acid solution, 17—electrode plate, 18—voltage stabilizing source. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0049] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0050] like Figure 3 As shown, if the initial plate (gradient stainless steel substrate 1) is prepared by powder sintering, the powders of various components are sequentially placed in a powder sintering mold 3 with a push rod 2, and the mold 3 is pressed and locked for sintering. After sintering, the pressure is released, the mold 3 is unlocked, and the gradient stainless steel substrate 1 is taken out by the push rod 2.
[0051] like Figure 4 As shown, if laser melting is used to prepare the initial plate (gradient stainless steel substrate 1), the printed substrate 5 is fixed on the forming cylinder 10, and the powders 4 of various components are placed in the powder cylinder 9 in reverse order, and the process parameters are set. After starting work, the substrate 5 drops to a single layer height, the powder cylinder 9 rises to make the powder higher than the working platform, the scraper 6 scrapes the powder 4 above the platform to the substrate 5, the laser 7 is turned on, and the melting area is adjusted by the galvanometer 8 to complete the single layer printing, and the excess powder 4 falls into the recovery cylinder 11. Repeat the above procedure until the preparation of the whole plate is completed, and the gradient stainless steel substrate 1 and the substrate 5 are removed together.
[0052] like Figure 5As shown, the initial plate (gradient stainless steel substrate 1) obtained by powder sintering or laser melting, or together with the substrate 5, is placed in an inert gas atmosphere for annealing to eliminate the internal residual stress caused by the preparation process.
[0053] like Figure 6 As shown, if laser melting is used to prepare the initial plate (gradient stainless steel substrate 1), the gradient stainless steel substrate 1 is separated from the base plate 5 by a molybdenum wire 12 through a wire cutting process.
[0054] like Figure 7 As shown, during the differential roller rolling process, the differential rollers are an upper high-speed roller 13 and a lower low-speed roller 14 of the same diameter, wherein the high-speed roller 13 contacts the high-chromium content stainless steel 1-1, and the low-speed roller 14 contacts the low-chromium content stainless steel 1-2, and the initial plate (gradient stainless steel substrate 1) is rolled and thinned to obtain a gradient thin plate.
[0055] like Figure 8 As shown, after stamping, electrochemical treatment is performed, the formed electrode plate 17 and the auxiliary electrode 15 are connected to the two ends of the voltage-stabilizing source 18, and two-stage electrochemical treatment is performed in the sulfuric acid solution 16 to improve the surface corrosion resistance.
[0056] Embodiment 1:
[0057] A conductive, corrosion-resistant, high-ductility, gradient stainless steel substrate and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0058] The four kinds of alloying powders shown in Table 1 were used for laser melting preparation, leaving a 0.2 mm thickness wire cutting allowance, and the corresponding process parameters of each layer are shown in Table 2; the initial plate formed by melting was annealed in an argon environment at a temperature of 750 °C and a processing time of 25 min, and then cooled naturally; the initial plate was separated from the substrate 5 by fast wire electrospark wire cutting, and the speed of the molybdenum wire 12 was 10 m / s to obtain an initial plate with a thickness of 1 mm; the initial plate was rolled using differential rollers, the diameters of the two rollers were both 80 mm, the speed of the low-speed roller 14 was 10 r / min, the speed of the high-speed roller 13 was 1.2 times the speed of the low-speed roller 14, the high-chromium content stainless steel 1-1 was in contact with the high-speed roller 13, and the low-chromium content stainless steel 1-2 was in contact with the high-speed roller 14, and the thickness was 0.2 mm after 5 rolling; the gradient thin plate after rolling was annealed in an argon environment at a temperature of 850 ℃, the treatment time is 30min, and it is naturally cooled to obtain a gradient stainless steel substrate 1 that can be used for stamping; the formed electrode plate 17 is placed in a 1 mol / L dilute sulfuric acid solution 16, and electrochemically treated at working voltages of 0.8 V / SHE and 1.4 V / SHE for 900 s and 3600 s respectively.
[0059] Table 1 Alloying powder composition and corresponding total thickness of Example 1
[0060] Number of layers Cr(wt.%) Ni(wt.%) Mo(wt.%) Mn(wt.%) C(wt.%) Si(wt.%) Fe(wt.%) Thickness(μm) margin 17.12 11.45 2.51 1.57 0.02 0.88 Bal. 200 1 17.12 11.45 2.51 1.57 0.02 0.88 Bal. 520 2 19.68 11.21 2.47 1.51 0.02 0.67 Bal. 180 3 22.95 10.85 2.17 1.37 0.02 0.72 Bal. 180 4 25.87 10.93 2.06 1.32 0.01 0.64 Bal. 120
[0061] Table 2 Process parameters corresponding to each layer in Example 1
[0062] Number of layers Laser power(W) Scanning speed (mm / s) Spot diameter(μm) Scanning pitch (μm) Layer thickness (μm) margin 180 850 60 65 30 1 180 850 60 65 30 2 220 850 60 65 30 3 260 850 60 65 30 4 300 850 60 65 30
[0063] A conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate is used for performance testing of a fuel cell bipolar plate, comprising the following steps:
[0064] The tensile properties of the gradient stainless steel substrate 1 were characterized by a uniaxial tensile test. A standard single-tension specimen with a gauge length of 30 mm and a width of 6 mm was prepared according to the national standard for testing. The test results showed that the engineering strain corresponding to necking was 32.7% and the engineering stress was 1096 MPa. For the homogeneous high-chromium sheet of the same size corresponding to the surface composition (high-chromium stainless steel 1-1), the engineering strain corresponding to necking was 15.7% and the engineering stress was 1182 MPa.
[0065] The contact resistance is used to characterize the conductivity of the bipolar plate. The measured contact resistance is 5.8 mΩ·cm 2 ;
[0066] The corrosion resistance of the bipolar plate is characterized by the self-corrosion potential in the potentiodynamic scanning polarization curve and the corrosion current density corresponding to 0.84 V / SHE. In the potentiodynamic scanning polarization curve, the higher the self-corrosion potential, the stronger the corrosion resistance, and the higher the corrosion current density corresponding to 0.84 V / SHE, the faster the corrosion rate: the self-corrosion potential is 0.242 V / SHE; the corrosion current density corresponding to 0.84 V / SHE is 0.63 μA / cm 2 .
[0067] Embodiment 2:
[0068] A conductive, corrosion-resistant, high-ductility, gradient stainless steel substrate and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0069] Five kinds of powders mixed with 316L and chromium powder in different proportions as shown in Table 3 were used for laser melting preparation, leaving a 0.2 mm thickness wire cutting allowance, and the corresponding process parameters of each layer are shown in Table 4; the initial plate formed by melting was annealed in an argon environment at a temperature of 900 ℃ and a processing time of 15 min, and then cooled naturally; the initial plate was separated from the substrate 5 by fast wire electric spark wire cutting, and the speed of the molybdenum wire 12 was 10 m / s to obtain an initial plate with a thickness of 0.5 mm; the initial plate was rolled using differential rollers, the diameters of both rollers were 80 mm, the speed of the low-speed roller 14 was 10 r / min, the speed of the high-speed roller 13 was 1.5 times that of the low-speed roller 14, the high-chromium content stainless steel 1-1 was in contact with the high-speed roller 13, and the low-chromium content stainless steel 1-2 was in contact with the high-speed roller 14, and the thickness was 0.2 mm after two rollings; the gradient thin plate after rolling was annealed in an argon environment at a temperature of 700 ℃ and a processing time of 20 min, and naturally cool to obtain a gradient stainless steel substrate 1 that can be used for stamping; the formed electrode plate 17 is placed in a 0.5 mol / L dilute sulfuric acid solution 16, and electrochemically treated at working voltages of 0.6 V / SHE and 1.2 V / SHE for 900 s and 3600 s, respectively.
[0070] Table 3 Mixed powder composition and corresponding total thickness of Example 2
[0071] Number of layers Cr(wt.%) Ni(wt.%) Mo(wt.%) Mn(wt.%) C(wt.%) Si(wt.%) Fe(wt.%) Thickness(μm) margin 16.89 11.52 2.33 1.21 0.03 0.76 Bal. 200 1 16.89 11.52 2.33 1.21 0.03 0.76 Bal. 260 2 20.19 11.28 2.14 1.26 0.02 0.72 Bal. 60 3 23.46 10.66 2.74 1.12 0.02 0.73 Bal. 60 4 25.94 10.85 2.03 1.57 0.03 0.65 Bal. 60 5 28.53 9.31 2.06 1.03 0.02 0.61 Bal. 60
[0072] Table 4 Process parameters corresponding to each layer of Example 2
[0073] Number of layers Laser power(W) Scanning speed (mm / s) Spot diameter(μm) Scanning pitch (μm) Layer thickness (μm) margin 180 850 60 90 20 1 180 850 60 90 20 2 225 900 60 90 20 3 270 950 60 90 20 4 315 1000 60 90 20 5 360 1050 60 90 20
[0074] A conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate is used for performance testing of a fuel cell bipolar plate, comprising the following steps:
[0075] The tensile properties of the gradient stainless steel substrate 1 were characterized by a uniaxial tensile test. A standard single-tension specimen with a gauge length of 30 mm and a width of 6 mm was prepared according to the national standard for testing. The test results showed that the engineering strain corresponding to necking was 30.5% and the engineering stress was 1164 MPa. For homogeneous high-chromium sheets of the same size with the same surface composition, the engineering strain corresponding to necking was 12.2% and the engineering stress was 1209 MPa.
[0076] The contact resistance is used to characterize the conductivity of the bipolar plate. The measured contact resistance is 7.4 mΩ·cm 2 ;
[0077] The corrosion resistance of the bipolar plate is characterized by the self-corrosion potential in the potentiodynamic scanning polarization curve and the corrosion current density corresponding to 0.84 V / SHE. In the potentiodynamic scanning polarization curve, the higher the self-corrosion potential, the stronger the corrosion resistance, and the higher the corrosion current density corresponding to 0.84 V / SHE, the faster the corrosion rate: the self-corrosion potential is 0.225 V / SHE; the corrosion current density corresponding to 0.84 V / SHE is 0.85 μA / cm 2 .
[0078] Embodiment 3:
[0079] A conductive, corrosion-resistant, high-ductility, gradient stainless steel substrate and a preparation method thereof, such as Figure 2 As shown, the following steps are included:
[0080] The four kinds of alloying powders shown in Table 5 were used for powder sintering preparation, the sintering temperature was 1000 ℃, the external pressure was 30 kPa, and the temperature was kept for 90 min; the sintered initial plate was annealed in an argon environment at a temperature of 800 ℃ for 20 min, and naturally cooled to obtain an initial plate with a thickness of 1 mm; the initial plate was rolled using differential rollers, the diameters of both rollers were 80 mm, the speed of the low-speed roller 14 was 12 r / min, the speed of the high-speed roller 13 was 1.2 times the speed of the low-speed roller 14, the high-chromium content stainless steel 1-1 was in contact with the high-speed roller 13, and the low-chromium content stainless steel 1-2 was in contact with the high-speed roller 14, and the thickness was 0.2 mm after 5 rolling; the rolled gradient thin plate was annealed in an argon environment at a temperature of 800 ℃ for 30 min, and naturally cooled to obtain a gradient stainless steel substrate 1 that can be used for stamping; the formed electrode 17 was placed in a 1 mol / L dilute sulfuric acid solution 16, and successively at 0.8 The electrochemical treatments were carried out for 900 s and 3600 s at working voltages of 0.1 V / SHE and 1.4 V / SHE.
[0081] Table 5 Mixed powder composition and corresponding total thickness of Example 3
[0082] Number of layers Cr(wt.%) Ni(wt.%) Mo(wt.%) Mn(wt.%) C(wt.%) Si(wt.%) Fe(wt.%) Thickness(μm) 1 17.15 11.92 2.83 1.68 0.02 0.65 Bal. 520 2 19.92 11.56 2.31 1.55 0.01 0.74 Bal. 180 3 23.16 11.20 2.21 1.28 0.02 0.66 Bal. 180 4 25.08 10.51 2.05 1.24 0.01 0.58 Bal. 120
[0083] A conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate is used for performance testing of a fuel cell bipolar plate, comprising the following steps:
[0084] The tensile properties of the gradient stainless steel substrate 1 were characterized by a uniaxial tensile test. A standard single-tension specimen with a gauge length of 30 mm and a width of 6 mm was prepared according to the national standard for testing. The test results showed that the engineering strain corresponding to necking was 30.2% and the engineering stress was 914 MPa. For homogeneous high-chromium sheets of the same size with the corresponding surface composition, the engineering strain corresponding to necking was 12.6% and the engineering stress was 1028 MPa.
[0085] The contact resistance is used to characterize the conductivity of the bipolar plate. The measured contact resistance is 9.3 mΩ·cm 2 ;
[0086] The corrosion resistance of the bipolar plate is characterized by the self-corrosion potential in the potentiodynamic scanning polarization curve and the corrosion current density corresponding to 0.84 V / SHE. In the potentiodynamic scanning polarization curve, the higher the self-corrosion potential, the stronger the corrosion resistance, and the higher the corrosion current density corresponding to 0.84 V / SHE, the faster the corrosion rate: the self-corrosion potential is 0.213 V / SHE; the corrosion current density corresponding to 0.84 V / SHE is 0.87 μA / cm 2 .
[0087] Among Examples 1 to 3, Example 1 has the highest necking elongation (32.7%) and the lowest corrosion current (0.63 μA / cm 2 ), the elongation and corrosion current values of Example 2 and Example 3 are similar, indicating that the use of alloyed powder for laser melting can achieve the preparation of better performance plates, and the performance will be reduced by in-situ melting alloying (Example 2) or powder sintering (Example 3) through powder mixing.
[0088] The corrosion current density of conventional 316L stainless steel sheet at 0.84 V / SHE is greater than 5 μA / cm 2 , compared with the corrosion current test results in Examples 1 to 3, it can be seen that the gradient thin plate prepared according to the method of this patent still has a significant improvement in corrosion resistance.
[0089] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A conductive, corrosion-resistant, high-ductility, gradient stainless steel substrate. It is characterized in that The two side surfaces of the gradient stainless steel substrate (1) are respectively low chromium content stainless steel (1-2) and high chromium content stainless steel (1-1), and the middle layer is a transition layer with a gradient transition of components along the thickness direction, wherein the thickness of the low chromium content stainless steel (1-2) accounts for 50-70% of the total thickness, the chromium content of the high chromium content stainless steel (1-1) is 25-30 wt.%, the thickness of the high chromium content stainless steel (1-1) accounts for 5-15% of the total thickness, and the rest is the transition layer; The preparation method of the conductive, corrosion-resistant, high-ductility component gradient stainless steel substrate comprises the following steps: (1) Stainless steel powders with different chromium contents are layered to obtain initial plates; (2) Annealing the initial sheet; (3) performing differential roller rolling on the initial plate to obtain a gradient thin plate; (4) annealing the gradient thin plate to obtain a gradient stainless steel substrate (1); In step (1), the stainless steel powders with different chromium contents are divided into low-chromium stainless steel powder, high-chromium stainless steel powder and transition layer powder, which are obtained by mixing 316L stainless steel powder and pure chromium powder, or directly using homogeneous pre-alloyed powder; The low chromium stainless steel powder is 316L stainless steel powder or homogeneous pre-alloyed powder with similar composition, and the proportion of each element in the low chromium stainless steel powder is Cr: 16-18 wt.%, Ni: 10-14 wt.%, Mo: 2-3 wt.%, Mn≤2 wt.%, C≤0.03 wt.%, Si≤1 wt.%, and the rest is Fe; The high chromium stainless steel powder is directly obtained by using homogeneous pre-alloyed powder, or by mixing 316L stainless steel powder with pure chromium powder. The proportion of each element in the high chromium stainless steel powder is Cr: 25-30 wt.%, Ni≤12.5 wt.%, Mo:1.5-3wt.%, Mn≤2 wt.%, C≤0.03 wt.%, Si≤1 wt.%, and the rest is Fe; The proportion of each element in the transition layer powder transitions layer by layer from high chromium stainless steel powder composition to low chromium stainless steel powder composition along the thickness direction, and the number of transition layers is 2-8 layers; The gradient stainless steel substrate (1) is electrochemically treated after being stamped; The electrochemical treatment includes a first stage and a second stage, wherein the applied voltage in the first stage is 0.5-0.8 V / SHE and the treatment time is 800-1000 s, and the applied voltage in the second stage is 1.0-1.4 V / SHE and the treatment time is 3200-3600 s. The solutions used in both stages are 0.1-1 mol / L dilute sulfuric acid solutions (16).
2. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 1, It is characterized in that The layered forming techniques in step (1) include powder sintering or laser melting.
3. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 2, It is characterized in that In step (1), the external pressure for powder sintering is 25-35 kPa, the holding time is 80-120 min, and the sintering temperature is 900-1100°C.
4. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 2, It is characterized in that In step (1), the laser spot diameter of the laser melting is 50-70 μm, the scanning interval is 65-105 μm, and the single layer melting thickness is 20-40 μm; The laser power for low-chromium stainless steel powder is 160-180 W, and the laser scanning speed is 700-900 mm / s; The laser power for high chromium stainless steel powder is 300-400 W, and the laser scanning speed is 800-1100 mm / s.
5. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 2, It is characterized in that After step (2), the initial plate obtained by laser melting is separated from the substrate (5) by wire cutting, wherein the wire cutting is a fast-wire electric spark wire cutting process, and the speed of the molybdenum wire (12) for wire cutting is 8-10 m / s.
6. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 1, It is characterized in that The annealing treatment in steps (2) and (4) is carried out in an inert gas environment, at a temperature of 700-900°C, for 15-30 min, followed by natural cooling.
7. The conductive, corrosion-resistant, high-ductility composition gradient stainless steel substrate according to claim 1, It is characterized in that In the differential roller rolling process in step (3), the differential rollers are a high-speed roller (13) and a low-speed roller (14) of the same diameter, the diameter of the differential roller is 80-100 mm, the high-speed roller (13) is in contact with the high-chromium content stainless steel (1-1), the low-speed roller (14) is in contact with the low-chromium content stainless steel (1-2), the rotation speed of the low-speed roller (14) is 5-20 r / min, and the rotation speed of the high-speed roller (13) is 1.2-1.5 times the rotation speed of the low-speed roller (14).
